2022
DOI: 10.3390/su14095154
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Competitiveness and Development Strategy of Korean Venture Companies in the Fourth Industrial Revolution Using SWOT/AHP

Abstract: This study derives the SWOT (Strength, Weakness, Opportunity, Threat) factors and competitiveness index necessary for Korean venture companies to succeed in the fourth industrial revolution. It suggests a SWOT strategy as well as an action plan in which the government and related parties prepare to secure global competitiveness, along with a very basic and systematic analysis. A total of 21 SWOT sub-factors were selected through a literature review and report analysis and were evaluated by various industry, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…As such, among the competencies required for talents in the knowledge and information society, digital competencies are being emphasized. Securing digital capabilities is important as well as checking the current infrastructure of Korea as it is expected that the presence or absence of market-leading advanced technology will determine the success or failure of individuals and nations in the future (Lee and Lee, 2022). Since 2018, Korea has implemented digital competency cultivating classes such as 'Computing Thinking Skills' in regular elementary and secondary education courses.…”
Section: Prior Research On Digital Competencymentioning
confidence: 99%
“…As such, among the competencies required for talents in the knowledge and information society, digital competencies are being emphasized. Securing digital capabilities is important as well as checking the current infrastructure of Korea as it is expected that the presence or absence of market-leading advanced technology will determine the success or failure of individuals and nations in the future (Lee and Lee, 2022). Since 2018, Korea has implemented digital competency cultivating classes such as 'Computing Thinking Skills' in regular elementary and secondary education courses.…”
Section: Prior Research On Digital Competencymentioning
confidence: 99%
“…Se sugiere una estrategia DAFO (Fuerza, Debilidad, Oportunidad, Amenaza), así como un plan de acción en el que el gobierno y las partes relacionadas se preparan para asegurar la competitividad global. Mediante la técnica AHP (Analytic Hierarchy Process) mostraron que la importancia de los 4 cuadrantes DAFO podía ordenarse como fuerza (48%) → oportunidad (25%) → amenaza (16%) → debilidad (11%) (D. Lee & Lee, 2022).…”
Section: Planteamiento Del Problema De La Competitividad Análisis Del...unclassified
“…Ghazinoory et al [26] argued that SWOT analysis is preferred because it presents a simple mechanism to align current and future potential opportunities with strengths and avoid threats by minimizing the effects of internal weaknesses. Whereas Lee and Lee [2] saw SWOT analysis as the essence of an organisation for resource and competency-based planning. Hill et al [8] underlined the advantages of SWOT analysis in developing strategies that are suitable to the changes in the external environment (the general and task environments) while maximizing the advantages of the internal factors.…”
Section: The Advantages Of (Swot) Analysis/ the Relationship With Org...mentioning
confidence: 99%
“…According to Kim and Han [1] during COVID-19, the rate of change in the economic modality has recently accelerated, resulting in unpredictability that crosses local market boundaries to reach the global scope. Lee and Lee [2] demonstrated that traditional competition games cannot be used to operate and compete in organizations. Survival, growth, and excellence aren't easy goals to reach if organizations don't know what changes might happen in the outside world and act as quickly as they can.…”
Section: Introductionmentioning
confidence: 99%